Dissociative symptoms reflect levels of tumor necrosis factor alpha in patients with unipolar depression - Bízik, Gustáv; Bob, Petr; Raboch, Jiri; Pavlat, Josef; Uhrova, Jana; Benakova, Hana; Zima, Tomas (Neuropsychiatric disease and treatment, 2014)
Recent evidence indicates that the nature of interactions between the nervous system and immune system is important in the pathogenesis of depression. Specifically, alterations in pro-inflammatory cytokines have been related to the development of several psychological and neurobiological manifestations of depressive disorder, as well as to stress exposure. A number of findings point to tumor necrosis factor alpha (TNF-α) as one of the central factors in these processes. Accordingly, in the present study, we test the hypothesis that specific influences of chronic stressors related to traumatic stress and dissociation are related to alterations in TNF-α levels. We performed psychometric measurement of depression (Beck Depression Inventory [BDI]-II), traumatic stress symptoms (Trauma Symptom Checklist [TSC]-40), and psychological and somatoform dissociation (Dissociative Experiences Scale [DES] and Somatoform Dissociation Questionnaire [SDQ]-20, respectively), and immunochemical measure of serum TNF-α in 66 inpatients with unipolar depression (mean age 43.1 ± 7.3 years). The results show that TNF-α is significantly related to DES (Spearman R=-0.42, P<0.01), SDQ-20 (Spearman R=-0.38, P<0.01), and TSC-40 (Spearman R=-0.41, P<0.01), but not to BDI-II. Results of the present study suggest that TNF-α levels are related to dissociative symptoms and stress exposure in depressed patients.